The relationship between health and religion from the standpoint of divine religions, the ancestors' medical sources and some literary works - Hossein Hatami (Shahid Beheshti University of Medical Sciences, 2016)
For downloading the full-text of this article please click here. The relationship between health and religion has been repeatedly highlighted and emphasized in Avesta, the Holy book of Zoroaster, which has been cited and referred to by our theist ancestors thousands of years before the Bible, the Torah and the Quran. There has been noticed a number of points about the effects of prayers and spirituality on the treatment of patients in this book. For example, it is mentioned in Ardibehesht section of this book that... For downloading the full-text of this article please click here.